2022
DOI: 10.1038/s41598-022-11760-1
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of prognostic risk model and drug sensitivity based on prognostic related genes of esophageal cancer

Abstract: At present, the treatment of esophageal cancer (EC) is mainly surgical and drug treatment. However, due to drug resistance, these therapies can not effectively improve the prognosis of patients with the EC. Therefore, a multigene prognostic risk scoring system was constructed by bioinformatics analysis method to provide a theoretical basis for the prognosis and treatment decision of EC. The gene expression profiles and clinical data of esophageal cancer patients were gathered from the Cancer Genome Atlas TCGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…There are also no relevant studies on COX6A2 and the prognosis of osteosarcoma. Moreover, there is only one paper on COX6A2 and cancer prognosis, which demonstrated that COX6A2 is a prognostic protective gene in esophageal cancer [ 25 ]. MTHFD2 is responsible for encoding a mitochondrial bifunctional enzyme that performs both methylenetetrahydrofolate dehydrogenase and methyltetrahydrofolate cyclohydrolase activities and is encoded by nuclear DNA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also no relevant studies on COX6A2 and the prognosis of osteosarcoma. Moreover, there is only one paper on COX6A2 and cancer prognosis, which demonstrated that COX6A2 is a prognostic protective gene in esophageal cancer [ 25 ]. MTHFD2 is responsible for encoding a mitochondrial bifunctional enzyme that performs both methylenetetrahydrofolate dehydrogenase and methyltetrahydrofolate cyclohydrolase activities and is encoded by nuclear DNA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asada et al suggested that ERO1B expression levels were associated with lung adenocarcinoma (LUAD) patient survival [ 50 ]. Another study showed ERO1B was one of the prognostic indicators of esophageal cancer (EC) [ 51 ]. The Receptor Expression-enhancing Protein 6 (REEP6), a member of the Yop1/Yip family, is associated with the enhancement of cell surface expressions and endoplasmic reticulum membrane shaping [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as found for FABP2, FABP3 mRNA was discovered in breast cancer culture cells where its expression is modulated by hormones and after exposure to media conditioned by fibroblasts ( 113 ). FABP3 protein expression is correlated with a poor prognosis in patients with gastrointestinal stromal tumors and esophageal cancer ( 22 , 29 ). Overall, FABP3 participation in tumor progression is uncertain mainly due to the fact that FABP3 may be expressed in tumor tissue as well as in nontumor tissue such as immune cells and stromal cells, and its role may be context specific in malignant progression.…”
Section: Fabp3mentioning
confidence: 99%